Social Biases and Equity Investment Decisions of Individual Investors: Behavior Finance Perspective - Sapkota, Mohan Prasad; Bhandari, Shiva (BMC Journal of Scientific Research, 2023)
Individual investors may not always pose a rational decision on stock market and heavily guided by their behavioral and social biases. This study is delineated to examine the role of social factors in the decision-making process of individual investors. This study is based on quantitative research approach and utilized a 5-points Likert type closed-end structured questionnaire survey to collect the data from 269 individuals, invested in the firms listed at Nepal Stock Exchange (NEPSE). This study utilized reliability analysis, descriptive statistics, Pearson correlation coefficient and ordinary least square (OLS) method. Evidence indicates that herding, social interaction and media effect shows the positive influences on equity investment decision process of the investors. Finally, this study justified that social biases play the significant role for equity investment decisions of the individual investors through excessive follow the humor of the market place, over or under reaction of the information about securities, follow the suggestions and recommendations of peers, friends, family members and neighbors along with highly depend upon news, social medias and information of so-called experts of capital market that leads to investment mistakes. Hence, investors should strongly follow the proper information about stock and market, utilize their own knowledge about information processing and analysis, and try to reduce the biases while making decisions through information analysis and processing that may downsize the irrational decisions.